Effectiveness of A Behavioral Counseling Lesson with Through Modeling Techniques to Improve The Personality Study Fellowship with Others - Ni Kade Sonia Pradesi; Kadek Suranata; I Ketut Dharsana (RedwhitePress)
This study aims to Determine the Effectiveness of behavioral counseling by modeling techniques through lesson study to improve the personality allied with others in first grade. In this study, using a kind of pseudo research (quasi-eksperimet). The study sample was taken by a modeling technique through lesson study. The collection of data personality allied with others collected by questionnaire in the scatterplot in the class. Questionnaires have been tested for validity and reliability to test the hypothesis used t-test. In a get t = 59.02 and the value table shows roomates 59.02 = 1, 717> 1,717 so that Ho refused and Ha accepted. There was significant difference given the value of the student questionnaire before and student services after the given service.